Penguatan Karakter Kemandirian Belajar melalui Pemanfaatan Teknologi Digital di PKBM Mandiri Bakti - Wahdatan Nisa; Dhea Tania Pangesti; Andin Dwi Kinanti; Hani Subakti (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to equip tutors and students at the Mandiri Bakti Community Learning Center (PKBM Mandiri Bakti) with the skills and independence to foster creativity and independent learning. This activity involves training using interactive online learning media such as Google Classroom, Canva, Zoom meetings, and Quizziz. Field observations indicate that many students still experience difficulties with online learning, such as not knowing which applications or platforms to use for online teaching and learning. Given these challenges, the goal of this activity is to train tutors and students to use digital technology in the online learning process. The training method uses socialization and mentoring. Socialization activities are conducted to convey the importance of tutors' and students' knowledge of learning technologies such as Google Classroom, Canva, Zoom meetings, and Quizziz, along with examples of their application in online learning. The training results show that through this training activity, tutors' creativity in creating online learning media has increased. The use of digital technology for students can also support independent learning. Through this community service activity, the process of developing an independent learning character among tutors and students in non-formal education is beginning to emerge. With this increase, the process of strengthening character through digital technology in the classroom becomes more effective, easier, and more enjoyable.